2020
DOI: 10.1002/anie.202009237
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Engineered Photoluminescence Tuning in Zero‐Dimensional Lead Bromide Trimer Clusters

Abstract: Zero‐dimensional (0D) hybrid metal halides are promising light emitters. However, it is still challenging to accurately design their structures with targeted photoluminescence properties. Herein, high pressure is used to change the self‐trapped exciton (STE) emission of 0D (bmpy)9[ZnBr4]2[Pb3Br11] (bmpy: 1‐butyl‐1‐methylpyrrolidinium). Under initial compression, the simultaneous contraction and distortion of photoactive [Pb3Br11]5− vary the equilibrium of STE emissions between different excited states, tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 39 publications
0
48
0
1
Order By: Relevance
“…High-pressure studies on metal halide perovskite (MHP) materials have revealed increases in optical tuning, 2,[9][10][11] bandgap optimization, 12,13 morphological control 6,14-17 and dramatic increases in quantum yields. [18][19][20][21] In particular, a new concept of pressure induced emission (PIE), whereby a nonluminescent material exhibits emission upon compression, was proposed in the research of compressed zero-dimensional (0D) perovskite Cs 4 PbBr 6 nanocrystals (NCs).…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure studies on metal halide perovskite (MHP) materials have revealed increases in optical tuning, 2,[9][10][11] bandgap optimization, 12,13 morphological control 6,14-17 and dramatic increases in quantum yields. [18][19][20][21] In particular, a new concept of pressure induced emission (PIE), whereby a nonluminescent material exhibits emission upon compression, was proposed in the research of compressed zero-dimensional (0D) perovskite Cs 4 PbBr 6 nanocrystals (NCs).…”
Section: Introductionmentioning
confidence: 99%
“…High pressure, as a physical means differing from chemical tailoring, can be used to adjust the electronic structure and crystal structure without changing the chemical composition. Recently, the high-pressure technique has been utilized to investigate the relationship between the structure and the properties for various types of perovskites. For example, the dramatic changes in structures under compression could result in unexpected emission at room temperature. However, most of these works have focused on the steady-state photophyscial properties, and the transient dynamic processes have not yet been revealed. The time-resolved PL and ultrafast transient absorption (TA) experiments can be used to investigate the transient dynamic processes, which is beneficial for revealing the mechanisms of these unexpected phenomena.…”
mentioning
confidence: 99%
“…Solid-state luminescent switching (SSLS) is of great interest and importance for adjustable light emitting diodes (LEDs), luminescent anticounterfeiting, imaging, sensors, and so forth. The switching can be realized by stimulation such as chemical vapor, mechanical force, and heat treatment. , In particular, the solvent-responsive structural transformation can be applied to gas sensing, anticounterfeiting, and rewritable luminescent paper arising from the solvatochromic PL. ,, For instance, Yam et al recently reported the luminescence color change in a gold-sulfido cluster accompanied by single-crystal-to-single-crystal (SCSC) transition under the selective stimulation of benzene/cyclohexane vapor . The 0D OIMHs can be excellent host materials for study of SSLS upon stimulation of small molecules.…”
Section: Introductionmentioning
confidence: 99%